Polychlorobiphenyl levels in the serum of cats from residential flats in Italy: Role of the indoor environment. Issue 9 (29th July 2018) - Serpe, Francesco Paolo; Fiorito, Filomena; Esposito, Mauro; Ferrari, Angelo; Fracassi, Federico; Miniero, Roberto; Pietra, Marco; Roncada, Paola; Brambilla, Gianfranco
ABSTRACT: The domestic cat ( Felis catus ) was used as a sentinel of exposure to polychlorobiphenyls (PCBs) in indoor urban environments y. Sera from 120 cats were pooled to form 30 different groups selected by age (<2 years; > 2 ≤ 8 years; > 8 years), sex, municipality (Bologna and Turin) and environment (indoor vs. outdoor). Test portions of 1 mL were analyzed by means of gas chromatography coupled to high-resolution mass spectrometry (GC-HRMS) for six selected indicators non-dioxin-like PCBs (∑6 PCBs: congeners #28, #52, #101, #132, #153 and #180) and the results were computed in the upper-bound mode. The internal dose of PCBs attributable to the cats' alimentary lipid intake ranged from 32.4 to 1, 446 ng/g (P50 165; mean 258). The Wilcoxon test revealed significantly lower PCB burden in "outdoor" groups than in "indoor" groups. Age correlated well with the heptachlorinated and most bio-accumulative congener, PCB #180, and slightly with hexachlorinated PCBs #138 and #153. Contamination attributable to house dust collected in 15 living-rooms ranged from 10.0 to 279 ng/g dry weight (P50 97.4; mean 94.4). Exposure estimates indicated a 0.6–16 ng/kg bw range of daily ∑6 PCB intake from a default value of 200 mg/cat of dust ingestion. The intake of PCBs due to dust ingestion fell within the same order of magnitude as that computed from a 60 g daily intake of commercial dry pet foods, while inhalation accounted for 0.21–8.2 ng/kg bw/day, on setting the nominal ∑6 PCB contamination in outdoor and indoor air at 0.37 and 15 ng/m 3, respectively. Italian indoor cats could be exposed to higher levels of ∑6 PCBs than the Reference Dose (RfD) of 10 ng/kg/bw/day; this supports the World Health Organization's statement that the quality of the indoor environment is a major determinant of health.